2021
DOI: 10.3389/fgene.2021.672149
|View full text |Cite
|
Sign up to set email alerts
|

Genome In Silico and In Vitro Analysis of the Probiotic Properties of a Bacterial Endophyte, Bacillus Paranthracis Strain MHSD3

Abstract: Spore-forming Bacillus species are gaining interest in human health recently, due to their ability to withstand the harsh environment of the gastrointestinal tract. The present study explores probiotic features of Bacillus paranthracis strain MHSD3 through genomic analysis and in vitro probiotic assays. The draft genome of strain MHSD3 contained genes associated with tolerance to gastrointestinal stress and adhesion. Cluster genes responsible for the synthesis of antimicrobial non-ribosomal peptide synthetases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 165 publications
(198 reference statements)
1
15
0
Order By: Relevance
“…In this study, B. altitudinis 1.4 showed a rate of 47% on average. Lower results were found by [59] when evaluating the cellular hydrophobicity of a B. paranthrancis MHSD3 isolate, with a rate of 29%. In the ndings of [63] the percentage hydrophobicity of a B. amyloliquefaciens AMS1 isolate was 68%.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, B. altitudinis 1.4 showed a rate of 47% on average. Lower results were found by [59] when evaluating the cellular hydrophobicity of a B. paranthrancis MHSD3 isolate, with a rate of 29%. In the ndings of [63] the percentage hydrophobicity of a B. amyloliquefaciens AMS1 isolate was 68%.…”
Section: Discussionmentioning
confidence: 83%
“…In 3 hours, the isolate B. altitudinis 1.4 showed 64.5% of auto aggregation. In the study by [59] results of 79% were found for the auto aggregation of Bacillus paranthrancis MHSD3.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, B. brasiliensis sp. nov. possessed an array of genes encoding virulence factors previously identified in many bacteria, and which are directly or indirectly related to biofilm formation ( carB [ 85 ], ricA [ 86 ], msrAB [ 11 ], and clpP [ 87 , 88 ]), adhesion ( cheB [ 87 ] and bpsC [ 89 ]), invasion ( fliP and fliI [ 90 ]; virB11 , [ 91 ]), LPS/O-antigen synthesis ( gmd [ 92 ]), synthesis of siderophore ( dhbA and dhbE [ 93 ]), and secretion and transport ( gspG [ 94 ] and xcpR [ 95 ]). Our strain also carried genes that encode isocitrate lyase ( icl ), elongation factor Tu ( tufA ), 2-dehydro-3-deoxyphosphooctonate aldolase ( kdsA ), and heat shock protein ( htpB ).…”
Section: Discussionmentioning
confidence: 99%
“…Autoaggregation, coaggregation and hydrophobicity of bacteria are considered to be important properties affecting their colonization in the intestine (Diale et al, 2021). Autoaggregation is the ability of the same cell types to self-adhere, and coaggregation is the combination of organisms of different species (Del Re et al, 2000;Kolenbrander, 2000).…”
Section: Discussionmentioning
confidence: 99%